2004
DOI: 10.1111/j.1834-7819.2004.tb00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment delays in paediatric dento‐alveolar trauma at a tertiary referral hospital

Abstract: Background: Paediatric dento-alveolar trauma is a common event. Delays in treatment can have adverse effects on long term outcomes and the aim of this study was to quantify the treatment delays in paediatric dento-alveolar trauma in a tertiary referral hospital. Methods: All cases of paediatric dento-alveolar trauma over a two year period from July 2000 to June 2002 were identified and the charts were reviewed retrospectively. All children presenting to the emergency department with dento-alveolar trauma withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
1
19
0
1
Order By: Relevance
“…In addition, there is a report that children who had trauma of soft tissues and luxations were brought to dental clinics faster and more frequently than children with fractures, because of bleeding tendency and interference with occlusion and chewing 31 . Our findings are in agreement with the observation that children who present to tertiary referral institutions for dental trauma treatment have more severe injuries than those treated elsewhere and that there is a large but potentially reducible delay between moment of injury and treatment 30 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, there is a report that children who had trauma of soft tissues and luxations were brought to dental clinics faster and more frequently than children with fractures, because of bleeding tendency and interference with occlusion and chewing 31 . Our findings are in agreement with the observation that children who present to tertiary referral institutions for dental trauma treatment have more severe injuries than those treated elsewhere and that there is a large but potentially reducible delay between moment of injury and treatment 30 .…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the time elapsed from the injury to dental treatment, results of the present investigation show that almost 40% of the study population had been referred for treatment in a period exceeding 24 hours, and dental treatment had been provided within the subacute approach for the majority of patients. Delay in treatment can have adverse effects on long term outcomes in dental trauma 30 , as shown in the investigations conducted in tertiary referral hospitals. In addition, there is a report that children who had trauma of soft tissues and luxations were brought to dental clinics faster and more frequently than children with fractures, because of bleeding tendency and interference with occlusion and chewing 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Dental injuries that cause pain to the patient should be considered urgent and treatment must be promptly provided to alleviate the discomfort. 5 Any hesitations that dentists might have in treating this type of patient merit investigating in order to develop ways to overcome this reluctance. 3 There is little published literature relating to possible barriers to treatment of dental trauma.…”
Section: S C I E N T I F I C a Rt I C L Ementioning
confidence: 99%
“…Similarly, Diaz et al 33 reported that only 3% of affected patients in their study were treated within 30 minutes and the most common form of storage was dry. Batstone et al 34 showed that only 5% of their patients received emergency treatment within three hours, including patients with immediate treatment needs. Similar results in the present study confirm the necessity of developing educational and prevention strategies.…”
Section: Discussionmentioning
confidence: 98%